(untitled) (Critical Journal of Social Sciences, 2026)
This study explores the impact of vocational training on women's empowerment in rural Sindh, focusing on the district of Sujawal. Drawing on qualitative fieldwork conducted under the project titled Strengthening The Socio-Economic Reliance Of Youth By Promoting Their Economic Self-Resilience (Project Code: PAK 1118), implemented by RDF with the support of WHH and funded by BMZ, the article documents how skill development in trades such as tailoring and beautician services has transformed the lives of marginalized women. As the individual researcher for the Gender Studies trainees, I led this research, focusing on case studies that highlight how economic independence fosters social mobility, self-confidence, and leadership among women. Gender equality and community development. In rural areas of Pakistan, particularly in Sindh, patriarchal structures and socio-economic barriers often hinder women's access to education, employment, and leadership. However, targeted vocational training programs have emerged as a transformative tool to empower women economically and socially.